EFFECT OF FOLIAR APPLICATION WITH CALCIUM, MAGNESIUM AND FERTILIZING WITH HUMIC ACID ON GROWTH , YIELD, AND STORAGE ABILITY OF POTATO TUBERS. - & Al-a'amry, Saaseea (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Two experiments were carried out, the first at the College of Agriculture - University of Baghdad during spring season 2017 Everest cv. class (Elite) was used to study the effect of foliar application of calcium and magnesium and addition of humic acid to the soil on potato growth and yield, The layout of the experiment was factorial within RCBD design using three replicates. Calcium and Magnesium sprayed with concentrations (0, 500, 1000 mg.L-1), while the  humic acid was added to the soil with (0, 0.75 gm.m2),  The second experiment included  storage of tubers produced from the spring season, with to study the effect of field treatments  on improving the storability of the tubers. The results showed that the treatment of calcium spray was superior a concentration of 1000 mg.L-1 in plant height, leaf area, weight of tuber, plant yield and protein %  in tubers after storage and reduced the percentage of damaged in tubers stored by 1.57%. The magnesium spray treatment with 1000 mg. L-1 exceeded the number of leaves, leaf area, number of tubers per plant, plant yield, the accumulation of dry matter and the percentage of  protein in the stored tubers. Humic acid with 0.75 gm.m2 was superior in the plant height , the tuber weight  and the single plant yield , the concentration of dry matter and the protein percentage in the stored tubers produced. The interaction treatment (500 mg.L-1 calcium + 0.75 gm2 of Humic acid + 0 mg.L-1 of Mg) was superior in the single  plant yield which 1.28 kg.plant-1.